2015
DOI: 10.1177/0898264315589574
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in the Association Between Body Mass Index Class and Annualized Medicare Expenditures

Abstract: Objective The aim of the study is to assess the relationship between body mass index (BMI) class and Medicare claims among young-old (65–69), old (70–74), and old-old (75+) adults over a 10-year period. Method We assessed costs by BMI class and age group among 9,300 respondents to the 1998 Health and Retirement Study (HRS) with linked 1998–2008 Medicare claims data. BMI was classified as normal (18.5–24.9), overweight (25–29.9), mild obesity (30–34.9), or severe obesity (35 or above). Results Annualized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…High levels of adiposity, manifested as being overweight to obese, is a significant and growing challenge to public health ( Clark et al, 2016 ). As a recognized risk factor for a wide range of chronic diseases such as metabolic syndrome, diabetes, hypertension, cardiovascular disease, stroke, and certain types of cancer ( Kopelman, 2000 ), obesity carries a heavy economic burden for governments and healthcare providers across the world ( Avenell et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…High levels of adiposity, manifested as being overweight to obese, is a significant and growing challenge to public health ( Clark et al, 2016 ). As a recognized risk factor for a wide range of chronic diseases such as metabolic syndrome, diabetes, hypertension, cardiovascular disease, stroke, and certain types of cancer ( Kopelman, 2000 ), obesity carries a heavy economic burden for governments and healthcare providers across the world ( Avenell et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…5 Clark and colleagues found that severely obese adults in particular (BMI>50) used 109% more healthcare funds than normal-weight adults. 6 This includes greater expenditures for durable medical equipment, emergency room visits, home health and hospice, nursing home, prescription drugs, as well as inpatient and outpatient visits. Additionally, obesity increases overall risk of disability and early retirement as a result of chronic illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…In der Berufsgruppe der Forstwirte konnte Rudolph (2013) Gesundheit und der Leistungsfähigkeit führt (Sluik et al 2008), ist ein erhöhter BMI mit steigenden Gesundheitskosten verbunden (Clark et al 2015). Trotz der hohen körperlichen (Åstrand 1987).…”
Section: Einen Weiterenunclassified